Robotic rectal resection: preliminary Russian experience - Khatkov,Igor (2018)
ABSTRACT Purpose: To outline the preliminary experience of the da Vinci® robotic system used in a Moscow tertiary colorectal referral center for an unselected range of benign and malignant rectal conditions. Methods: Prospective non-randomized single-center study which analyzed results of 26 robotic rectal resections performed between january 2014 and december 2016. Results: The cohort included 10 females and 16 males (mean total age 61.6 years). Three patients underwent surgery for benign rectal villous adenomas. The median overall ASA score was 4 (ranged from 2 to 5). Of the surgeries, there were 19 total mesorectal excisions with 6 patients undergoing a multivisceral resection. The mean operating time was 358 minutes with a mean blood loss of 203 mL. All total mesorectal excision specimens were adjudged according Philip Quirke classification as mesorectal plane - Grade 3 with a mean of 18.5 lymph nodes identified (from 12 to 35). Of these there were 10 patients (38.5%) with lymph node metastases. After surgery the average pain score was 2.1 out of 10 on the “Visual-Analogue Pain Intensity Scale” and 1.5 score out of 10 on the “Brief Pain Inventory with Quality of Life”. Anal continency after rectal resection with total mesorectal excisions estimated according Wexner Scale: 10 days after surgery average score was -3.1 and a 6 month after surgery -1.6 score. The median length of hospital stay was 11 days (from 10 to 15). Conclusion: Our initial experience with a totally robotic rectal resection has shown the technique to be safe and feasible, particularly in patients where conventional laparoscopic rectal resection would be anticipated to be challenging.